The Unity of Being (Wahdat al-Wujud), Mulla Sadra's Doctrine of the Existence of God - Afith Akhwanudin (Postgraduate Program, Universitas Islam Negeri (UIN) K. H. Abdurrahman Wahid Pekalongan, Indonesia, 2016)
The major concern in Islamic Philosophy, especially in the metaphysics is the reality of Being,that specifically studies about being itself. One of its purposes is to proof the existence of the Absolute Being, i.e., God. Regarding the proof for the existence of Absolute Being, arguments derived from pre-Islamic era were the argument about the first mover, which is not much valued. Much more powerful arguments have been advanced by the Muslim philosophers about these important issues. This doctrine which is widely known since the time of ibn ‘Arabi, basically is a view that states there is only one existence in this universe, i.e., God. Other beings, the world, and all other phenomenal existences do not really exist. That is, all of them do not separate from God. However, most people misunderstand this unity of Being (wahdat al-wujud) as pantheism, panentheism. The view (unity of being) does not equate everything (viewed as) other God with God, nor stating them are identical with God. Related to the unity of Being, other Muslim philosopher, Mulla Sadra conceives it in relation tothe multiplicity of existence as the rays of the sun in relation to the sun, which the rays of the sun are not the sun and at the same time are nothing but the sun. According to Sadra that existences are equal and the same for all objects, both concrete and abstract. However, the existence of God is pure, while the other has been added with the quiddity. This can be understood because, according to Sadra, the more perfect existence, the less essence would be shown. Here then comes the second principle, the gradation of being, which being not only one but is a hierarchy from the highest to the lowest level. The principle of the doctrine of unity is nothing but to proof that God is the Absolute Being, while the gradation of being is not other but as the principle of identity and difference among the beings.